A rare case of craniopagus parasiticus delivered vaginally at a district hospital - Chhabra, Komal Kuldeepsingh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Craniopagus Parasiticus is a very rare type of parasitic twinning. It has an incidence of only 4-6/10,00,000 births. Most of the babies with Craniopagus Parasiticus are still born with only few cases which survived after postpartum surgical separation. In Craniopagus Parasiticus the head of one of the twins is parasitic and protrudes from the head of the normal twin with an undeveloped or underdeveloped body. The skulls of the twins are fused but the body of one of the twins is not developed. The developed twin is known as the auto site while the undeveloped twin is the parasite. Age of the mother or certain nutritional factors have been implicated in the etiology of this type of twinning. This is a rare case report of a female baby with a parasitic craniopagus delivered vaginally at this district hospital. The patient was a fourth gravida 28 year old. There was antenatal polyhydramnios. The patient delivered preterm a still born female baby with a parasitic co-twin. In this case the heads of the twins were fused in temporal and parietal areas while the body of the parasitic twin was completely undeveloped. It was a morphologically female baby with rudimentary labia. The causes of Craniopagus Parasiticus are still not known. Scientists and researchers are continuing work to determine these and also to improve the prognosis and chances of post-surgical survival of these twins. Till present day however there have been only limited number of studies on Craniopagus Parasiticus owing to the rarity of the cases.